PENATAAN HAK ASASI ATAS PENDIDIKAN SAAT PANDEMI CORONA VIRUS DISEASE 2019 DI KOTA AMBON - S. F. Peilouw, Johanis; R. Pattipawae, Dazonda; J. Pieris, Henry (UNES Law Review, 2021)
The occurrence of the coronavirus 19 pandemic has caused all aspects of life to experience a downturn, including the fulfillment of the right to education. The purpose of the study was to study and analyze the impact of the covid 19 pandemic on the fulfillment of the right to education and to examine and analyze the arrangement of the right to education in the covid 19 pandemic in Ambon City. The research method used is normative legal research. The results of the study show that: 1) the impact of the Covid 19 Pandemic on the fulfillment of the Right to Education is that there is a gap in the process of fulfilling the right to education among students caused by students' economic problems, limited facilities to support the learning process from home, limited ability in mastering technology. 2) The structuring of the right to education in the Covid 19 pandemic in Ambon City is carried out through 2 (two) learning methods applied, namely online (online) and visits by teachers to students' homes.